Apakah Financial Behavior dan Intellectual Capital Memengaruhi Kinerja dan Sustainability UMKM di Kabupaten Pasuruan? - Nuraeni; Isro Triyawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Micro, Small and Medium Enterprises (MSMEs) have been recognized in the world view because they have a vital role in economic development in developed and developing countries. According to Law Number 20 of 2008 which defines that MSMEs or Micro, Small and Medium Enterprises are productive businesses owned by individuals or groups which have met certain criteria set by this law. Ministry of Cooperatives and Small and Medium Enterprises (Kemenkop UMKM) in 2023, there will be positive growth of MSMEs with 8.71 million units and Indonesia's GDP will reach 19,588 trillion rupiah in 2022. Therefore, optimal performance of MSMEs is necessary for sustainability and economic growth. The aim of this research is to determine and measure the influence of financial behavior and intellectual capital on the performance and sustainability of MSMEs in Pasuruan Regency. The sample selection in this study used purposive sampling of 64 fostered MSMEs in Pasuruan district. For statistical tests and data processing, use SmartPLS 4.0 by looking at the outer model and inner model values.